Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/masy.201300093
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Non‐Steroidal Anti‐Inflammatory Drugs (NSAIDs) in Poly(propylene) Matrices for Wound Healing Applications. The case of Ibuprofen

Abstract: Summary: Current work explores the possibility of incorporating common commercial non-steroidal anti-inflammatory drugs (NSAIDs) into poly(propylene) in order to develop biocompatible and bioactive surgical implants/sutures with controlled release characteristics. More particularly, we attempted to incorporate Ibuprofen, a widely utilized NSAID, into isotactic poly(propylene) (i-PP) films. Two basic methods of mixing were used and evaluated for their effectiveness; melt-mixing/melt-pressing and solvent casting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In some of our earlier studies, we introduced the controlled implementation of anisotropy as a method to regulate the release rate of low‐molecular‐weight substances entrapped in semicrystalline polymers. We have shown that the introduction of anisotropy in high‐density polyethylene samples leads to a reduction in the release rates measured in the case of triclosan incorporated into the polymeric matrix.…”
Section: Introductionmentioning
confidence: 99%
“…In some of our earlier studies, we introduced the controlled implementation of anisotropy as a method to regulate the release rate of low‐molecular‐weight substances entrapped in semicrystalline polymers. We have shown that the introduction of anisotropy in high‐density polyethylene samples leads to a reduction in the release rates measured in the case of triclosan incorporated into the polymeric matrix.…”
Section: Introductionmentioning
confidence: 99%